PENYULUHAN MANAJEMEN PEMASARAN BISNIS SYARIAH BAGI PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI DESA PAMIJAHAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR. - Rully Trihantana; Ria Kusumaningrum; Sri Hartati Mulya (SAHID EMPOWERMENT JOURNAL, 2023)
Micro, Small and Medium Enterprises or known as MSMEs are an important part of the economy of a country or region. Various efforts to develop MSMEs have been made, one of which is by generating and increasing new people or entrepreneurs in the MSME sector. Pamijahan Village, Pamijahan District, Bogor Regency also has many MSMEs. MSMEs that are easy to develop and can be found in this place are Culinary MSMEs. This is the potential that can stimulate the rural economy and absorb labor. However, there are also many MSMEs that have superior characteristics in their culinary delights in other areas, both villages that are nearby or far apart, which are currently relatively easy to reach with online delivery services. Therefore, sharia business marketing management is needed to improve the ability of MSMEs to market and sell their culinary delights.